Tweet tweet tick: a quantitative content analysis of risk communication about ticks on Twitter - Yang, Cheng-Xian; Baker, Lauri M.; McLeod-Morin, Ashley (Frontiers in Communication, 2024)
This study determined what information on Twitter (X) presented tickborne diseases and their prevention and investigated the relationships between content information and engagement rate. The escalating incidence of vector-borne diseases, particularly those transmitted by ticks, has emerged as a significant public health concern. Communicating tick risks effectively to the public has become an urgent issue. A quantitative content analysis was used to examine tick-related content to understand how this infectious disease was framed on social media, with 340 tweets comprising the final sample for this study. The results showed that in Twitter communication about tick risks, over half (55.3%) of the tweets lacked visual content. Among those with visuals, static photographs and illustrations/rendered images were the most commonly employed forms. Individual persons, news, and health/governmental organizations are the main tweeters. Additionally, most tweets use situational awareness, tool acquisition, and research frames and are in loss-frame. Approximately half (48.8%) of the tweets highlight adverse consequences or frame risk preparedness in negative terms. Tweets with visual aids have higher engagement rates, while those with URLs do not. Lastly, tweets use different preparedness response frames and tend to use different gain-/loss-frames. That is, tweets emphasizing situational awareness to alert the public about ticks and tickborne diseases predominantly utilize loss-frames, emphasizing higher risks compared to tool acquisition or research frames. The findings can improve the understanding of how social media present tick risks, which better communicate the disease and risk prevention effectively.